Isotope exchange rates in dissolved inorganic carbon between 40 degrees C and 90 degrees C - Weise, Andreas; Kluge, Tobias (Geochimica et cosmochimica acta, 2020)
Carbonate minerals are normally closely related to the stable and clumped isotope composition of the parent solution and are often assumed to record the equilibrium conditions in these proxies. Variations in e.g., temperature, pH or salinity lead to changes in the dissolved inorganic carbon (DIC) composition and to temporary deviations from expected isotopic equilibrium values. The exchange rate, at which the new equilibrium of stable and clumped isotopes is reached, has only been assessed experimentally for clumped isotopes between 5 degrees C and 25 degrees C and for delta O-18 up to 40 degrees C. In this study the delta O-18 and Delta(4)(7) evolution in the DIC pool of 0.1 molar sodium bicarbonate solutions at pH 8 and various temperatures (40 degrees C, 55 degrees C, 70 degrees C, 90 degrees C) was examined. At time intervals corresponding to the evolution of the DIC, a quantitative and instantaneous precipitation of the DIC was accomplished by adding strontium chloride and sodium hydroxide solutions. As the delta C-13 of the SrCO3 precipitates was constant and no significant non-first order trend was observed in Delta(47), delta O-18 and Delta(47) values could be simply fitted with an exponential approach to isotopic equilibrium. The temperature dependence of the rate constants was evaluated with the Arrhenius equation. The resulting rate constant based on the combined data points from delta O-18 and Delta 47 follows as k(T)[min(-1)] = exp((-1.00 +/- 0.15) . 10(4) *1/T+ (29 +/- 4)) The inferred exchange rate constants for Delta(47) are of the same order of magnitude as those of the oxygen isotopes and show a similar temperature dependence in the investigated temperature range. Our experimental results suggest that the isotopic equilibration of DIC in a solution with pH < 10 and elevated temperatures is rapid (at 70 degrees C: 4.5 min, at 90 degrees C: 36 s for 99% equilibrium) and that even in the case of short-term disturbances an equilibrated DIC composition is very likely for solutions in the diagenetic temperature range above 100 degrees C. In contrast, it is important to consider the generally long equilibration times at low temperatures (e.g., 2-6 days at pH 8.0-8.5 and 0 degrees C) and, in particular, at higher pH (e.g., >100 days at pH 11 and 0 degrees C).